2018
DOI: 10.1159/000488176
|View full text |Cite
|
Sign up to set email alerts
|

Gum Acacia Improves Renal Function and Ameliorates Systemic Inflammation, Oxidative and Nitrosative Stress in Streptozotocin-Induced Diabetes in Rats with Adenine-Induced Chronic Kidney Disease

Abstract: Background/Aims: The effect of treatment with gum acacia (GA), a prebiotic shown previously to ameliorate chronic kidney disease (CKD), in diabetic and non – diabetic rats with adenine – induced CKD has been investigated using several conventional and novel physiological, biochemical, and histopathological parameters. Methods: Diabetes mellitus was induced in rats by a single injection of streptozotocin (STZ). Diabetic and non – diabetic rats were randomly divided into several groups, and given either normal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 54 publications
4
25
0
Order By: Relevance
“…8), astrocytosis (Fig. 13) and calcium dysregulation in the cortex and hippocampus of the CKD mice may contribute to the observed depressive behaviour, since these inflammatory factors along with other associated pathophysiologies, which are prevalent in adenine model of CKD as well 56,60,98 , have been implicated in causing depression 99109 .…”
Section: Discussionmentioning
confidence: 99%
“…8), astrocytosis (Fig. 13) and calcium dysregulation in the cortex and hippocampus of the CKD mice may contribute to the observed depressive behaviour, since these inflammatory factors along with other associated pathophysiologies, which are prevalent in adenine model of CKD as well 56,60,98 , have been implicated in causing depression 99109 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the increasing frequency of prescribing mixtures of these herbs by practitioners of natural medicine calls for careful examination [ 10 ]. The use of these herbs results in a general improvement in the urinary system wellbeing through the reduction in blood urea nitrogen (BUN) and creatinine concentration [ 11 ], but the precise signaling cascades they elicit to repair renal cells remain obscure. Therefore, the benefits of combining the extracts of gum Arabic, parsley, and corn silk on the urinary system following a single one-off dose of amikacin are worth investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Manuscript to be reviewed the prevention of damage by regulation of the expression of anti-oxidant enzymes (Mori et al 2005). Models that have evaluated a single phase of CKD induced by adenine demonstrated an increase in serum NGAL levels relative to controls (Al Za'abi et al 2018;Ali et al 2018;. Another study that evaluated a three-phase model of CKD induced by adenine reported a significant increase in serum and urinary NGAL only in the presence of the damage inducer (Gil et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Cys-C has been proposed as a marker of renal function because it is freely filtered by the glomerulus and subsequently reabsorbed and degraded by proximal tubular cells (McMahon & Waikar 2013). Several studies of adenine-induced kidney damage have reported an increase in serum levels of Cys-C compared with the control group (Al Za'abi et al 2018;Ali et al 2015;Ali et al 2018;Ali et al 2017;Bokenkamp et al 2001;Thakur et al 2018); however, these studies reported only one phase of kidney damage. In the present study, it was found that the serum levels of Cys-C increased in each phase as the degree of renal damage increased, although histological evaluation suggested that the damage induced by FA in this study did not affect the structure of the glomerulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation